2012
DOI: 10.1080/15389588.2011.638683
|View full text |Cite
|
Sign up to set email alerts
|

Young and Unlicensed: Risky Driving Before Entering the Licensing System

Abstract: Prelicense drivers not only place themselves and other road users at risk at the time but also continue to do so through their subsequent risky driving. Prelicense driving should be discouraged, and parents should be encouraged to monitor car use and the driving behavior of their children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…Additionally, in all regressions, the more experienced P2 drivers were more likely to report than P1 drivers to have engaged in self-reported speeding behaviours. This is consistent with previous research that indicates that drivers are more likely to break the road laws as they progress through the graduated driver licensing system (S. Allen et al, 2015, online first;Bates et al, 2015, online first;Chapman, Masten, & Browning, 2014;Scott-Parker, Watson, King, & Hyde, 2012a). However, it is also likely that, just due to the greater amount of time they have spent on the road, they are more likely to have had a speeding ticket.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, in all regressions, the more experienced P2 drivers were more likely to report than P1 drivers to have engaged in self-reported speeding behaviours. This is consistent with previous research that indicates that drivers are more likely to break the road laws as they progress through the graduated driver licensing system (S. Allen et al, 2015, online first;Bates et al, 2015, online first;Chapman, Masten, & Browning, 2014;Scott-Parker, Watson, King, & Hyde, 2012a). However, it is also likely that, just due to the greater amount of time they have spent on the road, they are more likely to have had a speeding ticket.…”
Section: Discussionsupporting
confidence: 89%
“…Scott-Parker et al found that 12% of young people in Australia reported prelicence driving and were significantly more risky drivers than learner and provisional drivers. 23 Sivak et al showed a general reduced trend in the percentage of young persons with a driving licence in the USA; the percentage of licensed 19-year-olds dropped from 87.3% in 1983 to 75.5% in 2008 and 69.5% in 2010. 24 It is not known if this trend also indicates an increased number of unlicensed young drivers.…”
Section: Discussionmentioning
confidence: 99%
“…Unlicensed drivers not only place themselves and other road users at risk at the time, but also usually continue to be risky drivers in the future. 23 Therefore, pre-licence driving should be discouraged and parents should be encouraged to monitor car use and the driving behaviour of their children. 23 In this study, approximately half of the students drove a car, with the majority of these driving on a daily basis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, identifying just who to target, and when, appears to be the most promising direction for achieving further improvement in young driver road safety. Some way of reliably identifying these high-risk groups is therefore required, and recent research conducted by the authors (e.g., Scott-Parker et al, 2011a, 2012a, 2012b, 2012d, 2013 and others (e.g., Begg et al, 2010;Senserrick et al, 2010) are promising in this regard. Thereforewhilst broad countermeasures such as GDL merit continued application and refinement, it is timely that the concept of the problem young driverwithin the broader construct of the young driver problembe revisited.…”
Section: Graduated Driver Licensingmentioning
confidence: 99%